Soil-Transmitted Helminthiasis and Schistosomiasis in Children of Poor Families in Leyte, Philippines: Lessons for Disease Prevention and Control - Liwanag, Harvy Joy (Archīum Ateneo, 2017)
Objective Neglected tropical diseases (NTDs) continue to be a public health problem in the Philippines. We assessed the association of soil-transmitted helminthiasis (STH) and schistosomiasis with selected health-related and socioeconomic variables in four villages in Leyte, Philippines. Methods Stool specimens from 418 adults and 533 of their children from 209 families were examined through the Kato-Katz technique. Results STH and schistosomiasis were present in 64.6% and 12.5%, respectively, of study participants. Analysis through the generalized linear mixed model revealed a number of associations between infection in parents and their children. Findings indicate that years of disease prevention and control efforts in these areas have been unable to bring down prevalence in children and their parents. Eliminating NTDs as public health problems will require a systems thinking approach beyond implementation of vertical control programs alone.